2013
DOI: 10.3109/00365513.2013.787149
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin (NGAL) for the early detection of cardiac surgery associated acute kidney injury

Abstract: Urinary NGAL is a biomarker for very early risk stratification of AKI after cardiac surgery and may be useful as a basis for early interventional strategies to prevent CSA-AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
2
26
1
1
Order By: Relevance
“…Positive relationships with WBC count and resistin for both groups are in line with the view that serum NGAL could serve as an inflammatory marker in a range of clinical settings [45][46][47]. This lipocalin is expressed by neutrophils and various epithelial cells and has received attention as an acute kidney injury marker because of its early upregulation in the damaged tubular cells [7,48]. High expression of NGAL in atheromatous plaques and its role in inflammation might explain the previous finding that this biomarker could prove useful in discriminating between unstable and stable CAD patients [49,50].…”
Section: Discussionsupporting
confidence: 49%
“…Positive relationships with WBC count and resistin for both groups are in line with the view that serum NGAL could serve as an inflammatory marker in a range of clinical settings [45][46][47]. This lipocalin is expressed by neutrophils and various epithelial cells and has received attention as an acute kidney injury marker because of its early upregulation in the damaged tubular cells [7,48]. High expression of NGAL in atheromatous plaques and its role in inflammation might explain the previous finding that this biomarker could prove useful in discriminating between unstable and stable CAD patients [49,50].…”
Section: Discussionsupporting
confidence: 49%
“…The most studied and promising for routine clinical use of these markers is NGAL. Some studies evaluated pre-operative and post-operative 19 biomarkers, while some others evaluated intraoperative 20 temporal relation and predictive ability of several AKI biomarkers. As described in detail in a recent review, 21 serum and urine NGAL have been shown in a number of studies as independent predictors of development of postoperative AKI in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We could not find any study determined the independent predictors of urinary NGAL. Most of the studies addressed the value of UNGAL as a predictor of acute kidney injury [38]- [40]. We constructed a ROC curve to detect the cut off value of log UNGAL/Creatinine ratio to determine the normal value of log UNGAL/Creatinine ratio and it was found 1.035 Pg/ml with good AUC, sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%